Aligned Expression of IFI16 and STING Genes in RRMS Patients’ Blood - Helbi, Sobhan; Ravanbakhsh, Behnam; Karimi, Mohammad; Kooti, Wesam; Jivad, Nahid (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Objective: Multiple sclerosis (MS) is a chronic neurodegenerative disease of the central nervous system. The most common disease phenotype is Relapsing-Remitting MS (RRMS). Beta interferons are the first line of RRMS patients’ treatment. Interferon-inducible protein 16 (IFI16) as a DNA sensing molecule and its downstream complex stimulator of interferon genes (STING) play a critical role in the activation of type I interferons. Hence we aimed to evaluate the expression rate of IFI16 and STING in RRMS patients’ blood under a different type of IFNβ treatment. Methods: In the present study, 99 individuals participated. The participants were divided into 4 groups: 28 control subjects, 25 new cases of RRMS patients, 25 RRMS patients treated with IFNβ-1a (B1a), 21 RRMS patients treated with IFNβ-1b (B1b). The EDTA-treated blood samples were taken and transferred at standard conditions to the Cellular and Molecular Research Center of Shahrekord University of Medical Sciences, RNA was extracted and converted into cDNA. To evaluate the expression of IFI16 and STING, the Real-Time PCR method using SYBR Green/ROX qPCR master mix was performed done. The level of genes expression was measured using 2–ΔΔCt method. The obtained data were analyzed using SPSS v22 software. Results: Comparison of the IFI and STING mRNA expression in blood samples in association with gender and age showed no significant differences (p>0.05). Also, the evaluation of IFI16 mRNA level revealed that the IFI16 genes’ expressions were remarkably higher in the new case group compared to the control group, however, STING expression did not show any significant difference. The mRNA levels of IFI16 and STING in IFNβ-treated groups were significantly lower than the new case group (p<0.001). Also, the genes’ expressions in both the IFNβ-treated groups were significantly lower compared to the control group (p<0.001). In the assessment of the correlation of IFI16 and STING expressions with age and sex in different research groups, no statistically significant differences were seen (p>0.05). Conclusion: Perhaps the IFNβ therapy decreases the IFI16 and STING expression in a STINGdependent pathway as a negative feedback mechanism for regulation of the immune system and suppression of pro-inflammatory cytokines production. The important role of DNA sensing molecules and STING-dependent pathway in MS gives a new insight into future treatment based on STING-direct therapies.
Keywords: IFI16